Accounting Conservatism and Creditor Recovery Rate - Donovan, John; Frankel, Richard M.; Martin, Xiumin (The Accounting Review, 2015)
ABSTRACT We examine the relation between accounting conservatism and creditor recovery rates for firms in default. We also test the link between conservatism and the length of bankruptcy resolutions. We find that creditors of firms with more conservative accounting before default have significantly higher recovery rates, and that this positive relation is more pronounced for default firms that violated covenants before the default. We also find that conservative firms have higher asset productivity, shorter bankruptcy resolution, and a significantly higher probability of emerging from bankruptcy. These results suggest that accounting conservatism preserves firm value, leading to higher creditor recovery upon borrower default. JEL Classifications: M4; G32; G33; G34.